2016
DOI: 10.1021/acs.organomet.6b00451
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Systems in the Efficient Nickel-Catalyzed Kumada–Tamao–Corriu Cross-Coupling of Aryl Halides

Abstract: Highly active dinuclear nickel(I) complexes bearing bulky N-heterocyclic carbene ligands have been shown to be involved in the catalytic cycle of the Kumada−Tamao− Corriu cross-coupling reaction of aryl halides. The results of several stoichiometric reactions and kinetics experiments have revealed that monovalent and divalent dinickel species are the active species in the highly efficient, nickel-catalyzed, Kumada coupling reactions of aryl halides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 82 publications
2
77
2
Order By: Relevance
“…[7b] Matsubara and co-workers very recently showed that the latter complex triggers Kumada cross-couplings,a nd it was suggested that aN i I dimer or monomer may be involved in the process. [15] Smaller NHC Ni I monomers have also been shown to trigger CÀCa nd CÀN couplings. [9] Ap ronounced ligand effect was observed by Louie et al for the formation of Ni I or Ni II in reactions with (NHC)Ni 0 .…”
mentioning
confidence: 99%
“…[7b] Matsubara and co-workers very recently showed that the latter complex triggers Kumada cross-couplings,a nd it was suggested that aN i I dimer or monomer may be involved in the process. [15] Smaller NHC Ni I monomers have also been shown to trigger CÀCa nd CÀN couplings. [9] Ap ronounced ligand effect was observed by Louie et al for the formation of Ni I or Ni II in reactions with (NHC)Ni 0 .…”
mentioning
confidence: 99%
“…[13,20] For related dinuclear Ni I complexes,t here has been very recent evidence that carbon-based bridges may in fact be possible. [21] We calculated the predicted selectivities for an n-propyl-bridged Pd I dimer,w hich indicated ac lear C À Br addition preference.B oth C À Cl and C À OTf are predicted to be significantly disfavored (by DDG°= 5.8 and 2.8 kcal mol À1 ). Alternatively,P d 0 PtBu 3 may be active and our computations suggest preferential CÀBr addition (by DDG°= 4.4 and 8.3 kcal mol À1 for Cl and OTf).…”
mentioning
confidence: 99%
“…154 Matsubara and co-workers for the Kumada-Tamao-Corriu cross-coupling reaction. 111 In this case, the bimetallic core is stabilized by either one or two p-tolyl bridging ligands (B and C in Figure 17). DFT calculations showed the ability of the -p-tolyl ligand in B to slip into a  1 terminal position, allowing for the oxidative addition of the electrophile across the Ni-Ni bridge.…”
Section: Off-cycle Approach To Nickel Catalystsmentioning
confidence: 99%